Accessing the World: Adult Literacy Educators' Metaphors for Learners and Learning. (July 2015) - Konopasky, Abigail W.; Reybold, L. Earle
Adult educators are often part-time workers or volunteers and, as such, they must simultaneously negotiate multiple professional identities. This negotiation process may trigger conflict among professional identities, which can provide an opportunity for transformational learning. In this case study, the authors explore this conflict and learning through interviews with five female adult secondary educators. The authors use thematic analysis and metaphor analysis to explore participants' narratives of professional identity. Each participant narrates her unique professional situation with what the authors call metaphorical improvisation, creating new metaphors or using old metaphors in new ways. Moreover, all participants use metaphors of space and boundaries to narrate themselves as providing educational "access" for their students.